2014
DOI: 10.1051/matecconf/20141101012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of oil shale ash and coal ash on physic-chemical properties of CPJ45cement

Abstract: Abstract. We focused our research on recycling industrial wastes, fly ash (F.A), bottom ash (B.A) and oil shale ash (S.A) in cement production. The study concerns physico-chemical characterization of these products and the influence of their addition on the mechanical proprieties of the CPJ 45 cement. XRF allowed us to rank the three additives used according to their contents on major oxides. Coal ashes belong to the class F, and thus possess poozzolanic properties and oil shale ash belongs to the class C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…XRD analysis is usually performed to identify the degree of crystallinity and amorphousness of the material. The major minerals present in the parent sample are calcite, quartz, anhydrite, fluorapatite, and traces of clay minerals similar to what has been reported in previous studies [ 4 , 57 , 81 , 82 ]. Quartz was detected in all samples.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…XRD analysis is usually performed to identify the degree of crystallinity and amorphousness of the material. The major minerals present in the parent sample are calcite, quartz, anhydrite, fluorapatite, and traces of clay minerals similar to what has been reported in previous studies [ 4 , 57 , 81 , 82 ]. Quartz was detected in all samples.…”
Section: Resultssupporting
confidence: 82%
“…The temperature and duration limits simulate and summarize the parameters that were repeated in previous studies to determine their effect on this FOSA [ 46 , 57 , 58 , 59 ]. Lastly, the thermal-treated FOSA was sieved again to ensure the size of particles and remove the coarser and agglomerated materials using a 200 µm sieve.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the compressive strength decreases with the addition of fly ash (Figure 3). These results are in agreement with other studies [23,25], who found that the compressive strength decreases for additions of 5%, 10% and 20% of fly ash, and goes below the cement control values at an addition rate of 7%. This is due to the fact that class F fly ash is a slow reacting pozzolan, which means that it only starts to react noticeably after several weeks at 20°C of curing [26].…”
Section: Cmss-2017supporting
confidence: 93%